SISTEM KEAMANAN OPERASI LINUX UBUNTU IPTABLES SEBAGAI FIREWALL DI DINAS PENDIDIKAN KABUPATEN SERANG - Desmira Desmira (Universitas Bina Sarana Informatika, 2021)
Abstract - Network security is needed by both individuals and agencies. Threats from intruders who intend to destroy or steal important information or data through computer networks. Several types of network security consist of several ways, one of which is a firewall, many firewalls are chosen because they are more effective and easier to implement. Implementation of a firewall security system using the Iptables configuration as an alternative way to secure data from unscrupulous persons or parties. The purpose of this research is to make a firewall operating system using linux-based iptables that can meet the need for a computer network system, the benefit of this research is to reduce the level of risk of destruction or theft of files or information. The method used is in observation research, interviews and designing the Linux operating security system Ubuntu iptables as a firewall in the education office of the Serang district. The results obtained from this study are the use of Iptables configuration on the Ubuntu linux operating system can be done on LAN and Wifi cable connections, as long as all clients are in the same class, Iptables configuration can block client access to the server and can be done the other way around, namely blocking server access. towards the client. From the results of research conducted on several PCs with multiple network connectors, Iptables configuration can work and does not affect the OS used, because the Iptables configuration uses Linux OS where the client uses Windows OS.